The Effect of Workload and Work Environment on AVSEC Employee Performance - Romdhoni , Iqbal; Rahayu, Sri; Hardjanti , Wulandari (one million dreams corporation, 2025)
There are several aspects that are found to be able to influence the improvement of employee performance in aviation services. This study aims to understand how the interaction between workload and work environment can affect employee performance in the Angkasa Pura 1 Surabaya environment. Using a saturated sample of 50 employees at PT AVSEC Angkasa Pura 1 Sidoarjo which will be analyzed using multiple regression. The results of the study indicate that the workload found to be significant to employee performance but not for the work environment which has a negative and insignificant effect on employee performance. Other findings show that the variables of workload and work environment together are able to encourage increased employee performance. This study provides practical recommendations to organizations in an effort to improve employee performance